The autocrine motility factor receptor delays the pathological progression of Alzheimer’s disease via regulating the ubiquitination-mediated degradation of APP - Jingjing Zhang; Congcong Liu; Jing Liu; Yuting Cui; Yuli Hou; Qiao Song; Xiaomin Zhang; Xiaoling Wang; Qian Zhang; Min Cao; Wenchao Wang; Peichang Wang; et al. (Alzheimer’s Research & Therapy)
Abstract Background The ubiquitin-proteasome system (UPS) is responsible for most protein degradation and its malfunction is normally observed in neurodegenerative diseases, including Alzheimer’s disease (AD). The autocrine motility factor receptor (AMFR) is an E3 ubiquitin ligase that resides on the endoplasmic reticulum membrane and is involved in various essential biological processes. However, the role of AMFR in AD is still unidentified. Methods Behavioral experiments, including open-field test (OFT), novel object recognition test (NORT) and morris water maze test (MWMT) were conducted after adeno-associated virus (AAV) microinjection into AD model mice. Western blot, co-immunoprecipitation (Co-IP), qPCR and ubiquitination assay were used to analyze AMFR mediated ubiquitination degradation of amyloid precursor protein (APP). ELISA was employed to evaluate changes in amyloidogenic cleavage products of APP following upregulation or downregulation of AMFR in neural cells and analyze AMFR levels in serum and cerebrospinal fluid (CSF) of AD patients. Results The progressive decline in AMFR levels was found not only in the hippocampus of APPswe/PSEN1dE9 (APP/PS1) mice but also in the CSF and serum of patients with AD. Moreover, the interaction of AMFR and APP was observed both in hippocampal tissues and brain neurons. In addition, AMFR promoted the K11-linked polyubiquitination of APP to speed up its proteasomal degradation, resulting in decreased Aβ production. Importantly, AMFR overexpression largely rescued the cognitive and synaptic deficits in APP/PS1 mice. Conclusions Taken together, our results demonstrated that AMFR reduced Aβ production and alleviated cognitive impairment by promoting the ubiquitination-mediated degradation of APP. This study indicated that AMFR could have the potential to be a therapeutic target of early-stage AD.